Whole transcriptome sequencing reveals the functional regulation of chicken reproduction by lncRNAs, miRNAs, and mRNAs across the hypothalamus-pituitary-ovary axis - Li, Peifeng; Chu, Chengzhu; Hu, Lijuan; Zhang, Genxi; Wu, Pengfei; Zhang, Qi (Frontiers in Veterinary Science, 2025)
The hypothalamic–pituitary-ovarian (HPO) axis serves as the pivotal regulatory system governing reproduction in chickens. This study performed whole transcriptome sequencing on hypothalamus, pituitary, and ovarian tissues of Bian chickens to identify differentially expressed (DE) lncRNAs, miRNAs, and mRNAs (p < 0.05, FC > 2) between low- and high-laying groups. The hypothalamus exhibited 57 DE lncRNAs, 86 DE miRNAs, and 36 DE mRNAs; the pituitary showed the highest numbers with 206 DE lncRNAs, 234 DE miRNAs, and 528 DE mRNAs; while the ovary contained 111 lncRNAs, 230 miRNAs, and 62 mRNAs. GO functional enrichment analysis indicated that trans-target genes of hypothalamic and pituitary DE lncRNAs were enriched in cell proliferation Biological process (BP) terms (e.g., cell cycle, mitotic cell cycle). Hypothalamic miRNA targets clustered in metabolic regulation (cellular metabolic process), whereas pituitary miRNAs governed transport processes (nitrogen compound transport, intracellular transport). DE mRNAs showed BP terms enrichment in serotonin biosynthesis process, pituitary gland development, and DNA integration. KEGG pathway enrichment analysis revealed that lncRNA targets were significantly enriched in Progesterone-mediated oocyte maturation and Oocyte meiosis pathways in both hypothalamus and pituitary, with additional enrichment in Cell cycle and DNA replication. Notably, miRNA target genes showed conserved enrichment in metabolic regulation-related pathways (Metabolic pathways, Cysteine and methionine metabolism) across all three tissues. Key enriched pathways for DE mRNAs included Steroid biosynthesis, Cortisol synthesis and secretion, and Hippo signaling pathway. Finally, we constructed lncRNA-mRNA and miRNA-mRNA pairwise interaction networks, as well as ceRNA regulatory networks, through which we identified key regulatory networks targeting critical DE mRNAs, including GATA4, SMAD3, FOXL2, INHBA, POU1F1, LHX3, SPP1, SNAP25, COLQ, and AMPH. These results elucidate the multi-tissue molecular mechanisms underlying egg-laying performance in chickens, providing novel targets for improving poultry reproductive efficiency through marker-assisted breeding.